Now, mobile Web. - Biers, Dan; Slater, Joanna; Bickers, Charles (Far Eastern Economic Review, 2000)
Mobile communications and the Internet are two revolutionary technologies that are coming together in a manner that could change the business landscape of Asia. Wireless application protocol (WAP) provides direct connections from mobile devices to the Internet and other online services, and it also allows companies and their customers to communicate anywhere at anytime. WAP is available all over the world, but it is expected to impact rapidly in Asia, where there is greater penetration of cellular phones than personal computers. The advent of more advanced technology known as general packet radio service means that WAP is expected to take off in all major developed markets by the end of 2000. WAP promises to boost business efficiency greatly, with lawyers, consultants, and others able to keep in touch with clients and executives able to send e-mail from anywhere. However, analysts say WAP development is only beginning and that there are potentially many other business applications possible.